Cyberhooligans: a manifestação da violência das redes sociais - Bagni, Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Fans are a part of the sports context, and consequently generate influences on teams and athletes. Inside the fans group, there are some subdivisions, one of them are the organized fans. Although they are presented in many sports, this dissertation focuses on the soccer ones, whose actions, especially the violent ones, are a topic that is always on discussion as well as its relationship with soccer teams' board of directors. This relationship, however, is becoming weaken due to violent episodes. Besides that, the growth of social networks and its use by soccer organized fans, create an important mechanism to publicize its activities and to mark fights with other fans. Taking all these into consideration, this dissertation aims to analyze the official pages of some soccer organized fans on Facebook, to seek to categorize the content posted, to check for content related to the topic violence, to use the method of online content analysis, using techniques of nethnography and content analysis. The universe of this research was made up of Facebook fanpages of three differenet soccer organized fans' team of São Paulo city. We analyzed all the posts of these groups for the period of the year of 2014. For data analysis was used content analysis, which there was the categorization and prioritization of content and, after that, analysis and interpretation of data. The results are presented in percentage. We noted that the categories games, media and parties showed the most outstanding in relation to the overall outcome of the three organized fans analyzed. It was found out that the issue of violence happens in the background, as well as the club, which does not receive major highlight. Among the parties, that represent large number of the posts, we highlight the carnival, and we realized then, the existence of different subgroups within the organized fans. We understand that this work presents advances on this topic, especially in mapping...

As torcidas fazem parte do contexto esportivo e, consequentemente, geram influências sobre as equipe e atletas. Dentro do grupo torcidas, existem algumas subdivisões, uma delas é as torcidas organizadas, presentes em várias modalidades esportivas, porém neste caso serão consideradas as torcidas ligadas as equipes de futebol de campo. Suas ações são um tema que sempre é discutido, especialmente as ações violentas, e sua relação com a diretoria do clube também, já que existe uma ligação entre essas duas partes, relação esta que vêm diminuindo após certos episódios de violência. Com o crescimento das redes sociais, as torcidas também passaram a se utilizar delas, tanto para divulgar as suas atividades quanto para marcar brigas com outras torcidas. Frente a isso, este trabalho tem como objetivo analisar as páginas oficiais de algumas torcidas organizadas no Facebook, buscando categorizar os conteúdos postados verificando a existência de conteúdos referentes ao tema violência, por meio da análise de conteúdo online, utilizando-se de técnicas da netnografia e da análise de conteúdo. O universo desta pesquisa foi constituído pelas fanpages do Facebook de três torcidas organizadas de equipes de futebol da cidade de São Paulo. Foram analisadas todas as postagens destas torcidas referentes ao período do ano de 2014. Para a análise dos dados foi utilizado à análise de conteúdo, onde houve a categorização e hierarquização dos conteúdos e, após isso, análise e interpretação dos dados. Os resultados são apresentados em porcentagem. Notamos que as categorias jogos, mídia e festas foram as que apresentaram maior destaque em relação ao resultado geral das três torcidas. Foi verificado que a questão da violência acontece em segundo plano, juntamente com o clube, o qual também não recebe destaque principal. Dentre as festas que representam grande número das postagens...
Keywords: Sports - Sociological aspects; Esportes - Aspectos sociológicos; Redes sociais; Violência; Facebook (Recursos eletrônicos); Futebol - Torcedores; Ciberespaço; Esportes - Aspectos psicológicos